Isolation of antigenotoxic ursolic acid from Ixora coccinea flowers - Latha, PG; Nayar, MNS; Singh, OV; George, V; Panikkar, KR; Pushpangadan, P (Actualidades Biológicas, 2017)
Ixora coccinea L. (Rubiaceae) is a common shrub distributed throughout tropical India. The flowers of I. coccinea are extensively used in ayurvedic medicine. The hexane fraction of the flowers showed significant antigenotoxic properties. Chemical investigation of the above fraction has led to the isolation of the triterpenoid, ursolic acid as the active constituent.